Assessment of Factors Underpinning Employee’s Interest and Preference for Telecommuting in Lagos Island, Lagos, Nigeria - Koleayo Oluwafemi Omoyajowo; Adeyemi Adewale Akinola; Mary Adetutu Adewunmi; Grace Ojo-Emmanuel; Allen Ebosiem; Kolawole Ayodeji Omoyajowo; Aziba-anyam Gift Raimi (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2021)
Public awareness on environmentally sound practices viz-a-viz strategies that may also sustain a balanced work life culture cannot be overemphasized. Telecommuting represents one of those viable environmentally sound practices that offer flexibility to employees through working from their homes which to a great extent have improved employee’s productivity. This study assessed the level of awareness about telecommuting as well as the factors underpinning employee’s interest and preference for telecommuting in Lagos, Nigeria. A total of 220 responses from structured questionnaires was designed to capture the level of awareness, interest, readiness, and perception of employees towards telecommuting in Lagos Island, both descriptive and inferential analysis was used for the study. The study shows that 72% were aware of telecommuting and its associated benefits while about 90% opined that telecommuting will be suitable to their work. There was also a significant positive but weak relationship among employee’s preference for telecommuting and factors such as age, marital status, awareness about telecommuting, and the experience of traffic gridlock and its associated stress .This study concluded that with the high level of awareness of telecommuting, organisations should gainfully harness the wide array of prospects that accompanies the adoption of telecommuting which has the long term advantage of stimulating labor productivity.